Efectividad de un programa educativo en el nivel de conocimiento materno sobre alimentación complementaria - Araujo Cruz, Isaura Abigail (2021)
Quantitative, descriptive, correlational research of a pre-experimental type; It was carried out at the Alto Moche Health post, during the months of January and February 2020, in order to determine the effectiveness of the educational program “Comiendo Sanito” in the level of maternal knowledge about food complementary feeding in mothers of 5-month-old infants. The sample consisted of 15 mothers of infants who met the inclusion criteria. For data collection, the following instrument was used: Questionnaire to determine the mothers’ level of knowledge about complementary feeding, the information being obtained, processed and analyzed using the statistical correlation test of T-Student. The results are presented in single and double entry statistical tables. The following conclusions were reached: Before the application of the educational program, 60.0% of mothers had a medium level of knowledge, 26.7% had high knowledge and 13.3% had low knowledge. After the application of the educational program, 93.3% of mothers had a high level of knowledge and 6.7% had medium knowledge. There is a highly significant relationship between the educational program “eating healthy” and the level of maternal knowledge about complementary feeding (p=0.000).